(untitled) (UKLO Proceedings, 2025)
In today’s digital age, safeguarding critical infrastructure is fundamental to achieving sustainable development goals, as these infrastructures are the backbone of public services and economic stability. This article investigates how cybersecurity practices can align with sustainable development imperatives to protect critical infrastructure, focusing on public-private partnerships (PPPs) as a collaborative model. The article identifies and illustrates practical approaches to mitigate cyber risks, build resilience, and foster shared responsibility between the public and private sectors in securing critical infrastructure by emphasising PPPs. Previous studies in cybersecurity and infrastructure protection have often addressed technical defences or risk management in isolation without integrating sustainable development as a broader framework. Many have also yet to fully explore how collaborative governance models, such as PPPs, can facilitate resource-sharing and threat intelligence between public and private sectors. Consequently, the intersection of cybersecurity, critical infrastructure protection, and sustainable development still needs to be examined. The research employed a case study approach focusing on public-private partnerships for sustainable cyber resilience to address these gaps. This research offers a practical model for cross-sector collaboration in cybersecurity, directly contributing to SDGs 9, 11, and 16 by enhancing infrastructure resilience, promoting secure urban environments, and fostering solid institutional partnerships. Our findings indicate that regional cooperation in cyber governance could position the Western Balkans as a potential setter of the energy-digital agenda, facilitating energy security and European market integration. The article concludes that successful critical infrastructure protection requires diversification of energy sources, supply routes, and robust cybersecurity frameworks.